Efficacy of a balloon‐expandable vascular access system in transfemoral TAVI patients. Issue 7 (31st March 2016) - Millán, Xavier; Azzalini, Lorenzo; Khan, Razi; Cournoyer, Daniel; Dorval, Jean‐François; Ibrahim, Reda; Bonan, Raoul; Asgar, Anita W.
Abstract : Background: Vascular complications (VC) are a serious and frequent complication of transfemoral transcatheter aortic valve implantation (TAVI) and result in increased morbidity and mortality. It has been suggested that newly developed vascular sheaths may increase the ability to perform transfemoral TAVI in patients with normal and access‐limiting peripheral artery disease (PAD) and reduce vascular complications. Aims: We sought to assess the safety and efficacy of the 19 French (F) SoloPath balloon‐expandable transfemoral vascular access system in patients who underwent transfemoral TAVI at our center between 2011 and 2014. Methods and results: Single‐center retrospective study of 90 patients who underwent transfemoral TAVI with the use of the SoloPath sheath. Patients were categorized into two groups according to a sheath to femoral artery ratio (SFAR) of less than or equal to 1.05, or greater than 1.05. Overall, the incidence of major bleeding complications was low, 4.4%. No significant differences were found in technical or procedural success rates (100% in both groups and 100% vs. 91.3; P  = 0.09; respectively), total vascular complications (20.8 vs. 21.7; P  = 0.92) or total bleeding complications (20.8 vs. 30.4; P  = 0.36 between those with SFAR greater or less than 1.05. Conclusions: The use of the SoloPath balloon‐expandable sheath is feasible and safe even in patients with SFAR > 1.05, showing no increased vascular or bleeding complications compared to patients with larger vascular access. © 2016 Wiley Periodicals, Inc.